Sexual Risk Behavior among Youths of Nepal: Further analysis of Nepal Demographic Health Survey - Kakchapati, Sampurna; Oli, Sumina; Bhandari, Dikshika (Health Prospect, 2021)
Background: The period of youth is the time of major physical changes in the body that precedes psychosocial maturity. The curious mind of youths predisposes them to practice sexual risk behaviors. The aim of this study is to identify the sexual risk behavior and factors associated with sexual behaviors among youths of Nepal. Methodology: This was a retrospective analysis of 6524 youths aged 15-24 years using data obtained from the Nepal Demographic and Health Survey for the year 2016. The outcome was sexual behaviors and the determinants were socio-demographic characteristics and smoking. Statistical analysis was done using chi-square tests to assess statistically significant associations between determinants and outcome. In order to identify the most important determinants with the outcome, significant predictors in the univariate analysis were then included in logistic regression. Results: The prevalence of premarital sex among the youths was 5.2%, nearly half of them were sexually active and 5.5% had multiple sex partners. Variables that were significantly associated with premarital sex in the presence of other variables included male gender (AOR=6.3,95% CI=4.3,13.2) and smoker (AOR=2.4, 95%CI=1.8,3.16). Variables that were significantly associated with recent sexual activity in the presence of other variables included female gender (AOR=1.36,95%CI=1.18,1.58), age group (AOR=8.3,95% CI= 7.3,9.3), rural residence (AOR=1.4, 95% CI=1.26,1.62), illiterate youths (AOR=4.34,95% CI=3.27,5.76), poor wealth index (AOR=0.6, 95% CI=0.5,0.68) and smoker (AOR=3.38,95% CI=2.57,4.46). Variables that were significantly associated with multiple sexual partners in the presence of other variables included male gender (AOR=5.5, 95% CI=2.58,7.05) and smoker (AOR=2.2,95% CI=1.6,3.05). Conclusion: The male and smoker youths were more likely to practice all forms of sexual risk behaviors. This study recommends the need for further studies to understand the factors responsible for sexual risk behavior among youths. Furthermore, it is imperative to provide comprehensive sexuality education for youths.